Postgraduate training in orthodontics in the UK - Anwar Ali Shah; Jonathan Sandler (Elsevier, 2011)
This article briefly describes the postgraduate pathways in orthodontics in the United Kingdom. It is hoped that this will assist potential trainees who want to pursue postgraduate training to understand the different career pathways available to them. It may also add to the knowledge of some senior colleagues who can explain these career opportunities to their students, as not all potential trainees will have the opportunity to read this article. In the following pages we will discuss the different pathways leading to specialist qualification in orthodontics, in the United Kingdom. Keywords: Specialist training, Orthodontic training, Postgraduate training in UK